(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): Do we know the coaching method? Is the coaching method used in organizations? And does the coaching method have a positive effect on the growth of employees and thus on the growth of the organization? Purpose: The purpose is to show that the coaching method is important for the growth of the organization and thus for the personal growth of each employee. It is crucial for organizations to invest in their human capital. Method: A quantitative method was used with a prepared and implemented survey in the 1KA tool. For the article, we made a review of domestic and foreign literature on the topic of camping. Results: Respondents know the coaching method, this confirmed the first hypothesis. Also, the second hypothesis was confirmed, that organizations do not use the coaching method in their work or management. The third hypothesis was also confirmed by the respondents, namely that the coaching method has a positive effect on the organization. Using the example of the good production practice of Pošta Slovenije, we demonstrated the impact of coachwork on the organization. Organization: The organization and managers get an insight into the coaching method, what are the benefits of this method for employees and the organization, advantages, disadvantages and opportunity. Society: The personal growth of each employee is the essence of the organization and is the key to the success of the individual as well as the organization and society. It is important to realize how important human capital is. Originality: The research gives a general view of the knowledge of the coaching method in our country. Limitations/Future Research: The research was limited to a small number of respondents. To expand the survey, the survey could be published on several Internet links and thereby involve more people. But we could add other questions on the topic of coaching. To analyze the case study, we could also take other examples of good manufacturing practice.